Dual sourcing : with arbitrary stochastic demand and stochastic lead times - Schimpel, Ulrich (KIT Scientific Publishing, 2010)
Companies with high-performing supply chains enjoy essential competitive ad- vantages. However, supply chain management faces an environment of rising risk that endangers these competitive advantages. One of the reasons is to outsource parts of their business. This bears the risk of significantly increased lead times and lead time variability. It is the impact of lead time variability on inventory management that is the central aspect of this book. It describes a mathematical model for dual sourcing with two reorder points, shows the deviation between stochastic and deterministic calculations in a sensitivity analysis, and investigates different relaxations of a traditional dual-sourcing policy.